2017
DOI: 10.11609/jott.3301.9.9.10656-10661
|View full text |Cite
|
Sign up to set email alerts
|

<b>Winter food habits of the Golden Jackal <I>Canis aureus</I> (Mammalia: Carnivora: Canidae) in Patna Bird Sanctuary, Uttar Pradesh, India</b>

Abstract: C omm u n fi c a t fi o n W fi n t e r ff o o d h a b fi t s o ff t h e G o l d e n J a c k a l C a n fi s a u r e u s (M amm a l fi a : C a r n fi v o r a : C a n fi d a e ) fi n P a t n a B fi r d S a n c t u a r y , U t t a r P r a d e s h ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In fact, the amount of civets in the jackal diet in SWS was the highest ever reported for small carnivores in a jackal diet. Only two previous studies found civets in jackal diets, one in India ( Khan et al 2017 ) and another in Pakistan ( Shabbir et al 2013 ), although in both instances they comprised relatively small amounts of the jackal diets (1% and 9%, respectively). Other small carnivores have been detected in low amounts in previous studies of jackal diets, including domestic dogs and domestic cats ( Supplementary Data SD1 ), indicating jackals can regularly prey on smaller carnivores.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the amount of civets in the jackal diet in SWS was the highest ever reported for small carnivores in a jackal diet. Only two previous studies found civets in jackal diets, one in India ( Khan et al 2017 ) and another in Pakistan ( Shabbir et al 2013 ), although in both instances they comprised relatively small amounts of the jackal diets (1% and 9%, respectively). Other small carnivores have been detected in low amounts in previous studies of jackal diets, including domestic dogs and domestic cats ( Supplementary Data SD1 ), indicating jackals can regularly prey on smaller carnivores.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies in wetlands show that jackals exhibit bimodal activity with one of the two peaks in the afternoon (Shankar et al 2020;Shameer et al 2022). Jackals are highly adaptive mammals and are commonly recorded from wetlands (Khan et al 2017). They exhibit phenotypic plasticity or altered coat patterns as an adaptation to human-dominated landscapes (Shameer et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative Analysis: Scat samples of each carnivore species were categorized by season (Summer: April to September; Winter: October to March). Each prey type in the diet was expressed as frequency of occurrence (FO), defined as FO = S/N where s is the number of occurrences of each prey type and N is the total occurrences of all prey types in all samples (Khatoon et al, 2017;Khan et al, 2017;Khatoon et al, 2019) For each carnivore species and season we calculated prey species diversity (H'), prey richness (S), the total number of animal prey species consumed by each carnivore in a specific season) and prey evenness (E, calculated as E = H'/lnS) (Khatoon et al, 2019). Prey species diversity was calculated as H' = -Σ [pi × ln pi] where pi represents the relative percentage of each prey item i.…”
Section: Identification Of Plant Mattermentioning
confidence: 99%